The Influence of Environmental Factors on the Prevalence of Myopia in Poland - Maciej Czepita; Damian Czepita; Wojciech Lubiński (Journal of Ophthalmology)
Purpose. In the paper, we describe and discuss the results of epidemiological studies concerning myopia carried out in Poland. Materials and Methods. Results from the examination of 5601 Polish school children and students (2688 boys and 2913 girls) aged 6 to 18 years were analyzed. The mean age was 11.9 ± 3.2 years. Every examined student had undergone the following examinations: distance visual acuity testing, cover test, anterior segment evaluation, and cycloplegic retinoscopy after instillation of 1% tropicamide, and a questionnaire was taken. Results. We have found that (1) intensive near work (writing, reading, and working on a computer) leads to a higher prevalence of myopia, (2) watching television does not influence the prevalence of myopia, and (3) being outdoors decreases the prevalence of myopia. Conclusions. The results of our study point to insufficiency of accommodation contributing to the pathogenesis of myopia.